2022
DOI: 10.3390/v14020284
|View full text |Cite
|
Sign up to set email alerts
|

Neutralizing Antibodies Limit Cell-Associated Spread of Human Cytomegalovirus in Epithelial Cells and Fibroblasts

Abstract: Human cytomegalovirus (HCMV) can cause severe clinical disease in immunocompromised individuals, such as allograft recipients and infants infected in utero. Neutralizing activity of antibodies, measured as the ability to prevent the entry of cell-free virus, has been correlated with the reduction in HCMV transmission and the severity of HCMV-associated disease. However, in vivo HCMV amplification may occur mainly via cell-to-cell spread. Thus, quantifying the inhibition of cell-to-cell transmission could be im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Since these individuals only had gB antibody responses (since these were pre-transplant sera taken from HCMV seronegative individuals vaccinated with gB) it suggests that other gB antibody responses induced by the vaccine could also be important 17,36 . Work is ongoing to try and identify them but we highlight, for example, recent work that demonstrates an anti-AD-5 antibody that is a potent inhibitor of gB fusogenic activity which could contribute to the limiting of viral cell-tocell spread 37,38 . Indeed, there is a certain hubris to imply a single immune response is required for complete protection from HCMV infectionthe key will be identifying the important responses and finding ways to induce them effectively whilst eliminating the induction of poorer, competing responses.…”
Section: Discussionmentioning
confidence: 99%
“…Since these individuals only had gB antibody responses (since these were pre-transplant sera taken from HCMV seronegative individuals vaccinated with gB) it suggests that other gB antibody responses induced by the vaccine could also be important 17,36 . Work is ongoing to try and identify them but we highlight, for example, recent work that demonstrates an anti-AD-5 antibody that is a potent inhibitor of gB fusogenic activity which could contribute to the limiting of viral cell-tocell spread 37,38 . Indeed, there is a certain hubris to imply a single immune response is required for complete protection from HCMV infectionthe key will be identifying the important responses and finding ways to induce them effectively whilst eliminating the induction of poorer, competing responses.…”
Section: Discussionmentioning
confidence: 99%
“…Further, pentamer dependent cell-tocell spread is resistant to antibody neutralisation compared to cell-free spread which further supports this mode of dissemination in vivo (Murrell et al, 2017). It must be noted that other studies have observed antibody neutralisation of cellto-cell spread using different virus strains which have altered ratios of trimer and pentamer in their envelopes, which may explain these differences and potentially offer insights into different mechanisms of spread (Li et al, 2015;Klupp et al, 2017;Reuter et al, 2022). Curiously, virions lacking the assembly tegument protein UL99 were still able to spread cell-to-cell in fibroblasts, despite a defect in virion envelopment, which may indicate a distinct mechanism (Silva et al, 2005).…”
Section: Figurementioning
confidence: 54%
“…Our end goal is to define HCMV neuropathogenesis and identify approaches to limit it using human neural tissue models. Considering that tropism is aligned with intrinsic features of the virions, we tested the impact of antibodies against viral glycoproteins previously shown to be neutralizing (15, 22, 23). We pretreated NPCs for 1 hr prior to infection with antibodies against HCMV gB or gH at 4 µg/ml.…”
Section: Resultsmentioning
confidence: 99%